Chitin/Metal‐Organic Framework Composites as Wide‐Range Adsorbent. Issue 14 (23rd June 2021) - Tovar Jimenez, Gabriel I.; Valverde, Ainara; Mendes‐Felipe, Cristian; Wuttke, Stefan; Fidalgo‐Marijuan, Arkaitz; Larrea, Edurne S.; Lezama, Luis; Zheng, Fangyuan; Reguera, Javier; Lanceros‐Méndez, Senentxu; Arriortua, María I.; Copello, Guillermo; et al.
Abstract: Composites based on chitin (CH) biopolymer and metal‐organic framework (MOF) microporous nanoparticles have been developed as broad‐scope pollutant absorbent. Detailed characterization of the CH/MOF composites revealed that the MOF nanoparticles interacted through electrostatic forces with the CH matrix, inducing compartmentalization of the CH macropores that led to an overall surface area increase in the composites. This created a micro‐, meso‐, and macroporous structure that efficiently retained pollutants with a broad spectrum of different chemical natures, charges, and sizes. The unique prospect of this approach is the combination of the chemical diversity of MOFs with the simple processability and biocompatibility of CH that opens application fields beyond water remediation. Abstract : Clean it up : Chitin (CH) macro‐ and mesoporous biopolymer and metal‐organic framework (MOF) microporous nanoparticles are combined to obtain a macro‐ to microporous sorbent able to retain pollutants from the Ångstrom to nanometer scales. CH/MOF composites outperform the adsorption capacities of the average sum of their CH and MOF components due to their improved textural properties and diverse surface chemistry effects.